Himachalol induces apoptosis in B16-F10 murine melanoma cells and protects against skin carcinogenesis. (10th May 2020) - Shebaby, Wassim; Elias, Andree; Mroueh, Mohamad; Nehme, Bilal; El Jalbout, Nahia Dib; Iskandar, Rita; Daher, Joey C.; Zgheib, Michelle; Ibrahim, Pascale; Dwairi, Vanessa; Saad, Jean Michel; Taleb, Robin I.; et al.
Abstract: Ethnopharmacological relevance: Cedrus libani A. Rich ( C. libani ) is majestic evergreen Mediterranean conifer growing in the mountains of Lebanon. The ethnobotanical and traditional uses of cedar wood oil traces back to ancient times for the treatment of various ailments including cancer. Previous work in our laboratories revealed that himachalol (7-HC), a major sesquiterpene isolated from C. libani, possesses potent cytotoxic activity against various human cancer cell lines as well as promising anti-inflammatory effect in isolated rat monocytes. Aim of the study: The present study aims to elucidate the mechanism of action behind the cytotoxic activity of 7-HC against murine melanoma cells (B16F-10) and evaluates its chemopreventive effect against chemically-induced skin carcinogenesis in mice. Materials and methods: 7-HC was extracted and purified from Cedrus libani wood. Cell viability was evaluated using WST-1 kit. Cell cycle analysis and apoptosis were assessed by Flow cytometry using propidium iodide (PI) and fluorescein Isothiocyanate (FITC)-conjugated Annexin V/PI staining respectively. Apoptosis related protein were quantified using western blot. The chemopreventive activity of 7-HC was evaluated for 20 weeks using a DMBA/TPA induced skin carcinogenesis model in Balb/c mice. Results: 7-HC displayed a potent anti-proliferative activity against the melanoma cells with an IC50 of 8.8 μg/ml and 7.3 μg/ml at 24 and 48 h, respectively. Co-treatment with Cisplatin did not show any synergistic or additive effect on cell viability. Flow cytometry analysis using PI revealed that 7-HC treatment (5 and 10 μg/ml) induces the accumulation of cells in the sub-G1 phase and causes a decline in cell populations in the S and G2/M phases. Annexin/PI staining also reveals that 7-HC treatment significantly increases the percentage of cells undergoing early and late apoptosis. Western blot analysis shows that 7-HC treatment decreases the level of the anti-apoptotic protein Bcl-2 and increases the level of the pro-apoptotic protein Bax. A reduction in the level of phosphorylated Erk and Akt was also observed. 7-HC via topical (2.5%), intraperitoneal (10, 25 and 50 mg/kg) or gavage (50 mg/kg) treatment revealed a significant decrease in papilloma volume with no adverse effect on liver and kidney function. Conclusions: The present study demonstrates that 7-HC treatment protects against chemically-induced skin carcinogenesis, promotes cell cycle arrest and induces apoptosis partially through an inhibition of both the MAPK/Erk and PI3K/Akt pathways. Graphical abstract: Image 1